2018
DOI: 10.1007/s12032-018-1210-8
|View full text |Cite
|
Sign up to set email alerts
|

Droplet digital PCR using HER2/EIF2C1 ratio for detection of HER2 amplification in breast cancer tissues

Abstract: Breast cancers with amplification and overexpression of human epithelial growth factor receptor 2 (HER2) are associated with poor prognosis, and targeted for anti-HER2 therapy. Immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) are currently the recommended methods to asses HER2 overexpression/amplification. Droplet digital PCR (ddPCR), a highly accurate method to quantify DNA copy number, is potentially a robust alternative for HER2 diagnostics. In the FISH assay and most of previous ddP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Compared with the previous studies that measured HER2 ratios of gastric cancer patients using ddPCR [19][20][21][22][23][24] , our study covered the largest cohort to the best of our knowledge; moreover, we worked with paired samples of formalin-fixed and paraffin-embedded (FFPE) tissues and preoperative plasma cfDNA. We used EIF2C1 as the reference gene, and ddPCR using the HER2/EIF2C1 ratio demonstrated that it can assess HER2 status accurately 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the previous studies that measured HER2 ratios of gastric cancer patients using ddPCR [19][20][21][22][23][24] , our study covered the largest cohort to the best of our knowledge; moreover, we worked with paired samples of formalin-fixed and paraffin-embedded (FFPE) tissues and preoperative plasma cfDNA. We used EIF2C1 as the reference gene, and ddPCR using the HER2/EIF2C1 ratio demonstrated that it can assess HER2 status accurately 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma is one promising biomarker the predictive value of ctDNA, in patients with metastatic melanoma, by quantitative analysis of plasma mutations of BRAF V600 has unique properties as a monitoring tool during treatment with BRAF/MEK inhibitors, both as a predictor of response and treatment resistance [74,75]. LB based on ctDNA detection, such as digital PCR (ddPCR) assays, have demonstrated the clinical utility of ddPCR in determining HER2 mutations in breast cancer [38,58,76]. Finally, in pancreatic cancer, Cohen et al have shown that the analysis of KRAS gene mutations, using ctDNA, had greater diagnostic power than any single marker as carcinoembryonic antigen (CEA); carbohydrate antigen 19-9 (CA19-9); cancer antigen 125 (CA125) but it's not yet a reality in clinical practice [77].…”
Section: Applications Of Liquid Biopsy's Biomarkersmentioning
confidence: 99%
“…Absolute HER2 copy number can be determined by ddPCR without the need for calibration. So, ddPCR technique may be useful as an alternative to FISH and MLPA in HER2 diagnosis [ 103 ].…”
Section: Applications In Cancer Research and Molecular Testingmentioning
confidence: 99%